Peran Guru Kelas dalam Pelayanan Bimbingan Konseling sebagai Motivasi Berprestasi Peserta Didik - Ningrum, Mareta Septi Ningrum Septi; Mareza, Lia; Nugroho, Agung (Jurnal Ilmiah Psyche, 2019)
This study aims to determine the role of classroom teachers in providing counseling guidance services to students, so that students at SD Negeri Wiradadi have achievement motivation in competitions. Based on the observation of researchers at SDN Wiradadi that SDN Wiradadi has several charter and trophies, as in the previous four years starting from 2016-2019. The championship in the Sokaraja District level competition that was obtained by the school in 2016/2017 contained 13 trophies. In 2017/2018 there were 8 championship trophies. In 2018/2019 there were 13 competition trophies. Schools often get championships to compete with other schools. The championship was obtained by students representing schools to take part in the competition, besides that research was conducted to find out the factors that influence students so that they could excel. Data collection techniques using observation, interviews, and documentation. Analysis of the data used is descriptive qualitative. This research was conducted with 10 respondents, namely the Principal, 3 class teachers and 6 students. The results showed that students in SD Wiradadi State already had high achievement motivation. Obtaining championships in students get support and guidance from a teacher. The role of the teacher in shaping students to be outstanding using counseling guidance services. Teachers have ways, approaches and strategies for students in implementing the counseling guidance service to form students so that they have high achievement motivation. Factors that can influence students to be outstanding are socioeconomic status factors, parenting practices, the education system, self-skills and teacher expectations.